Occupation. (2014) - London, Tanja
Abstract : occupation is a screendance that explores a state of "uprootedness" in the context of the events of the Iraq War and the World Financial Crisis. The film utilizes the metaphor of a historic building and its astonishing relationship to its foundation to illustrate the second wave of erosion of American democracy after 9/11. The film features three movers: two dancers and one building. In 2009, this five million-pound building underwent an engineering feat when it was raised eleven feet off its foundation and moved in one fell swoop. Interleaved footage of the dancers and the building in motion illustrates their correlation—a mounting tension that speaks to democracy in the U.S. being shaken, uprooted, and redefined underneath people's feet. Dizzying changes silence oppositional voices occupying public spaces. Pursuing everyday occupations equals prevailing war in the name of democratic values. But do we still live in a democracy?